Dynamic Alteration of the Loss Function in Convolutional Neural Networks for Medical Image Segmentation - Souza, Vinicius Ferreira de; Machado, Alexei M. C. (Anais do Simpósio Brasileiro de Computação Aplicada à Saúde (SBCAS); 2026: Anais do XXVI Simpósio Brasileiro de Computação Aplicada à SaúdeDO - 10.5753/sbcas.2026.21408, 2026)
This work presents a method for training convolutional neural networks (CNNs) based on the dynamic alteration of the loss function that guides model optimization. First, a comparative analysis of six different loss functions applied to CNNs for medical image segmentation is conducted. Through experiments with the colon cancer dataset from the Medical Segmentation Decathlon, distribution-based functions (Focal Loss, TopK Loss, and Binary Cross-Entropy) and region-based functions (Dice Loss, IoU Loss, and Tversky Loss) are evaluated. The results demonstrate that distribution-based functions consistently outperform region-based functions. Furthermore, the dynamic alteration of the functions achieved an increase in accuracy of up to 12% when compared to composite approaches. Qualitative analysis revealed that this approach not only improves quantitative metrics but also enhances the visual quality of segmentation. These findings provide valuable insights for optimizing CNN performance in medical image segmentation and contribute to the development of more accurate solutions in AI-assisted diagnosis.